Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.14338/ijpt-16-0000.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Commissioning of a Pencil Beam Scanning Treatment Planning System for Proton Therapy

Abstract: Purpose: In this report, we present the commissioning and validation results for a commercial proton pencil beam scanning RayStation treatment planning system. Materials and Methods: The commissioning data requirements are (1) integrated depth dose curves, (2) spot profiles, (3) absolute dose/monitor unit calibration, and (4) virtual source position. An 8-cm parallel plate chamber was used to measure the integrated depth dose curves by scanning a beam composed of a single spot in a water phantom. The spot prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 13 publications
(13 reference statements)
2
53
0
Order By: Relevance
“…It has been shown that, especially at large depths, the Bragg peak chamber is not large enough to capture the whole laterally scattered dose . Therefore, the IDD curves have to be corrected by means of MC simulations …”
Section: Detectors For Absorbed Dose In Nonreference Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that, especially at large depths, the Bragg peak chamber is not large enough to capture the whole laterally scattered dose . Therefore, the IDD curves have to be corrected by means of MC simulations …”
Section: Detectors For Absorbed Dose In Nonreference Conditionsmentioning
confidence: 99%
“…85,114,146,147 Therefore, the IDD curves have to be corrected by means of MC simulations. 85,109,115,148 The more recent Stingray chambers (IBA Dosimetry) mitigates this effect 149 thanks to the larger radius (6.0 cm) as compared with the Bragg peak chamber (4.08 cm), therefore it reduces the need of MC correction. The Stingray chamber can also be moved remotely and with 0.1 mm steps when mounted on the Blue Phantom2 system (IBA Dosimetry).…”
Section: F Ionization Chambersmentioning
confidence: 99%
“…For high energies, when the nuclear halo is depth dependent, this effect has been studied and characterized with Monte Carlo‐based dose calculation algorithms . With more widespread implementation of clinical Monte Carlo algorithms, and enhanced corrections for model‐based algorithms, the halo effect at depth can be modeled within 1–2% accuracy for high‐energy beams .…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics provide an opportunity for optimal target dose coverage, that is, uniformity and conformity, with reduced integral dose and sparing of surrounding healthy tissues . In Pencil Beam Scanning modality, target coverage in the plane orthogonal to the beam propagation is typically achieved by sweeping the beam by a set of scanning magnets . Coverage along the longitudinal direction is achieved by repeatedly changing the beam energy (energy stacking), covering the target layer by layer from distal to proximal depths .…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 Coverage along the longitudinal direction is achieved by repeatedly changing the beam energy (energy stacking), covering the target layer by layer from distal to proximal depths. 2,4,5 A number of factors can compromise the target dose coverage. 2 For a given prescribed range, delivering inaccurate beam range can influence the target coverage and the dose to critical structures by undershooting or overshooting of the target distal margin.…”
Section: Introductionmentioning
confidence: 99%